Decreased DNA Repair Ability: A Mechanism for Low Early Embryonic Development Potential of Oocytes From Overweight Patients After Fertilization in IVF Cycles - Li, Hui; Wang, Huan; Zhu, Jing; Xu, Jianmin; Jiang, Yuqing; Chen, Wenhui; Sun, Yingpu; Yang, Qingling (Frontiers in Endocrinology, 2021)
BACKGROUND: Whether female BMI impacts the DNA repair ability in the oocytes after fertilization has not been investigated. This study aims to assess the early embryo quality and reproductive outcomes of oocytes from overweight women when fertilized with sperm with varying degrees of DNA fragmentation. METHODS: A total number of 1,612 patients undergoing fresh autologous in vitro fertilization (IVF) cycles was included. These patients were divided into two groups according to maternal body mass index (BMI): normal weight group (18.5–24.9 kg/m2; n=1187; 73.64%) and overweight group (≥25 kg/m2; n=425; 26.36%). Each group was then subdivided into two groups by sperm DNA fragmentation index (DFI): low fragmentation group (＜20% DFI, LF) and high fragmentation group (≥20% DFI, HF). Laboratory and clinical outcomes were compared between subgroups. RESULTS: For the normal-weight group, there was no statistical significance in embryo quality and reproductive outcomes between the LF and HF groups. But in the overweight group, significantly lower fertilization rate (LF: 64%; HF: 59%; p=0.011), blastocyst development rate (LF: 57%; HF: 44%; p=0.001), as well as high-quality blastocyst rate (LF: 32%; HF: 22%; p=0.034) were found in the HF group, despite the similar pregnancy rates (LF: 56%; HF: 60%; p=0.630). CONCLUSIONS: Decreased DNA repair activity in oocytes may be a possible mechanism for the low early development potential of embryos from obese patients in in vitro fertilization cycles.